Parenting Insight Program: Leveraging WhatsApp Collaboration Between Teachers and Parents to Foster Student Independence in Elementary Schools - Dinda Tri Septiyan; Ali Armadi; Muhammad Misbahudholam AR (STAI Hubbulwathan Duri, 2025)
The increasing emphasis on student autonomy in 21st-century education necessitates effective collaboration between schools and families. In elementary education, however, fragmented communication between teachers and parents often hinders the development of student independence. This study investigates the impact of teacher–parent collaboration via WhatsApp on student independence through the Parenting Insight Program. A correlational quantitative approach with an explanatory design was used. Data were collected from 30 fifth-grade students, their teachers, and parents in an elementary school in Sumenep, Indonesia. Instruments were based on validated theoretical constructs. Pearson correlation analysis assessed the relationship between collaboration indicators and student independence. The analysis revealed significant positive correlations between teacher–parent communication, joint problem-solving, and parental involvement with students’ responsibility, initiative, and decision-making (r = 0.72–0.85, p 0.01). Furthermore, religiosity was negatively correlated with aggressiveness (r = –0.71, p = 0.001), suggesting that internalized spiritual values may support emotional self-regulation and reduce behavioral issues. The findings highlight WhatsApp's potential as a low-cost, culturally adaptive tool for enhancing home–school collaboration. The Parenting Insight Program offers a structured model that integrates digital communication into character education. Teacher–parent collaboration via accessible technology like WhatsApp can foster student independence and personal development. The Parenting Insight Program exemplifies how ethical, systematized digital engagement can strengthen educational outcomes and inform school–family partnership strategies.